2016
DOI: 10.1111/jam.13286
|View full text |Cite
|
Sign up to set email alerts
|

Novel haemoglobin-derived antimicrobial peptides from chicken (Gallus gallus) blood: purification, structural aspects and biological activity

Abstract: The obtained results expand the perception of the role of haemoglobin in a living system, describing it as a source of multifunction substances. Additionally, the data presented in this paper may contribute to the development of new, cost-effective, antimicrobial agents.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 52 publications
0
6
0
Order By: Relevance
“…A breach in the outer membrane of Gram-negative bacteria was detected using a hydrophobic fluorescent probe. 1- N -phenylnaphthylamine (NPN) is a hydrophobic, neutrally charged substance normally impermeable into the outer membrane, but if the molecules of NPN internalize in phospholipid environments, its fluorescence strongly increases [ 27 , 28 ].…”
Section: Resultsmentioning
confidence: 99%
“…A breach in the outer membrane of Gram-negative bacteria was detected using a hydrophobic fluorescent probe. 1- N -phenylnaphthylamine (NPN) is a hydrophobic, neutrally charged substance normally impermeable into the outer membrane, but if the molecules of NPN internalize in phospholipid environments, its fluorescence strongly increases [ 27 , 28 ].…”
Section: Resultsmentioning
confidence: 99%
“…The accumulation of certain probes will reflect the size of the lesions. This approach has been successfully used to determine actions of various AMPs including temporin L , magainin , maculatin , and hemocidines .…”
Section: Resultsmentioning
confidence: 99%
“…It was hypothesized that human blood contains a factor that suppresses toxin-production. Today, it is known that animals’ blood is a source of various peptides including hemocidins, which are the cationic peptide fragments derived from hemoglobin (Mak et al, 2000; Arroume et al, 2008; Vasilchenko et al, 2016). Further studies of the antitoxic effects of hemoglobin showed the ability of globin chains to inhibit all known types of Agr-quorum sensing systems of S. aureus .…”
Section: Effects Of Sub-inhibitory Concentrations Of Antimicrobial Pementioning
confidence: 99%